2018
DOI: 10.1016/j.envint.2018.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metals and metal mixtures in Bangladesh: Exploring environmental sources in the Health Effects of Arsenic Longitudinal Study (HEALS)

Abstract: Introduction: Environmental exposure to toxic metals and metalloids is pervasive and occurs from multiple sources. The Health Effects of Arsenic Longitudinal Study (HEALS) is an ongoing prospective study predominantly focused on understanding health effects associated with arsenic exposure from drinking water. The goal of this project was to measure a suite of elements in urine to better understand potential exposure patterns and to identify common environmental sources of exposure among this semi-rural Bangla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…As a result of commercial uranium mining and insufficient remediation, many tribal communities located in the Southwestern United States are exposed to varying degrees of contaminant metal mixtures arising from abandoned uranium mines (AUMs) [4][5][6]. Exposure to metals through drinking water has been linked to adverse health outcomes [7][8][9][10], and residential proximity to AUMs is associated with an increase in circulating inflammatory biomarkers [11]. However, the contribution of wind-blown dust exposure on vascular and other health outcomes remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of commercial uranium mining and insufficient remediation, many tribal communities located in the Southwestern United States are exposed to varying degrees of contaminant metal mixtures arising from abandoned uranium mines (AUMs) [4][5][6]. Exposure to metals through drinking water has been linked to adverse health outcomes [7][8][9][10], and residential proximity to AUMs is associated with an increase in circulating inflammatory biomarkers [11]. However, the contribution of wind-blown dust exposure on vascular and other health outcomes remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, smoking cessation is recommended as one of the lifestyle modi cations for managing SUI (52). However, we are exposed to Cd from a wide range of sources (53), and reducing passive exposure requires effective government measures and policies to control it (17).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, public health research has focused on the potential adverse effects of metal mixtures , with an emphasis on mixtures containing cadmium (Cd), manganese (Mn), lead (Pb), and the metalloid As. ( Claus Henn et al, 2014 ) This mixture of metalloid/metals has previously been found in Bangladeshi street dust, ( Safiur Rahman et al, 2019 ) drinking water, and in urine samples collected from participants of the Health Effects of Arsenic Longitudinal Study (HEALS), ( Sanchez et al, 2018 ) whose offspring were recruited for participation in this study of adolescents, known as the Metals, Arsenic, & Nutrition in Adolescents study (MANAs). Additionally, this investigation includes selenium (Se) in its metalloid/metal mixture, as it has been observed to attenuate the adverse effects of As.…”
Section: Introductionmentioning
confidence: 99%